Mandibular bone restructuring after of octacalcium phosphate transplantation: histological, immunohistochemical and ultrastructural aspects - Chelpanova, I.V. (Морфологія / Morphologia / Morfologìâ, 2022)
This article presents the research results of the histological, immunohistochemical, and ultrastructural characteristics of bone-ceramic regenerate after octacalcium phosphate transplantation into an experimental defect in the rabbit mandible, since complete and high-quality regeneration of maxillofacial bones, its mechanisms and dynamics remain not fully understood, need clarification and detailing. Aim. To study in an experiment the dynamics of histological, immunohistochemical, and ultrastructural changes in the lower jaw bone after its traumatic injury with subsequent replacement of the defect with octacalcium phosphate. Methods. Experiments were conducted on 45 male rabbits aged 6-7 months, weighing 2.5-3.0 kg. 20 animals constituted the control group, and 20 the experimental group. Another 5 intact animals were used to study the normal structure of the bone tissue of the studied area of the mandible. The control group included animals with a bone tissue defect that healed under a blood clot. The experimental group consisted of rabbits where the bone defect was filled with modified natural octacalcium phosphate (OCP-N). Post-traumatic bone tissue status within the defect area was monitored for 84 days using the following methods: bone defect modeling, light-optical assessment of the histostructure of decalcified bone sections, immunohistochemical determination of the expression of markers CD34, Calcitonin, Ki-67, transmission electron microscopy. Results and conclusion. The osteoconductive effect of exogenously modified natural octacalcium phosphate is realised through accelerated neoangiogenesis with migration of osteoprogenitor cells from the periphery towards the deep zone of the bone-ceramic regenerate and, also, through the formation of numerous osteogenic islands throughout its volume within the first three weeks post-implantation. Four weeks post-implantation of OCP-N, anastomosis of the islands of desmal osteogenesis with each other and with the regenerated trabeculae of the native bone results in the formation of a continuous cancellous structure of the regenerate. This structure consists of woven bone trabeculae and fragments of exogenous octacalcium phosphate. Simultaneously, periosteal regeneration occurs on the implant surface, with activation of osteoclasts in the peripheral trabeculae of the bone-ceramic regenerate. The remodeling processes extend from the periphery to the deep zone of the regenerate, which leads to the replacement of the woven bone trabecular tissue with primitive bone plates with accelerated cytodifferentiation of numerous osteocytes. 5 weeks after implantation, osteocytes with ultrastructural signs of maturity appear near the restored mineralized osteons of the native bone and on the surface of the implanted octacalcium phosphate granules in the inner areas of the regenerate. Eight weeks post-implantation of OCP-N, compaction of the newly formed trabeculae near the regenerated periosteum leads to normalization and stabilization of the osteon histoarchitecture in the peripheral zones of the regenerate, which becomes fully integrated with the native bone. In the deeper zone, the slower processes of membranous osteogenesis are replaced by active remodeling with the formation of immature osteocytes and primitive bone lamellae. Twelve weeks post-implantation of OCP-N, the majority of the bone-ceramic regenerate contains a fully restored osteocyte lacuno-canalicular system. In the deeper zone of the regenerate, some foci of coarse fibrous bone tissue remain. These contain a moderate number of activated osteoclasts, secretory active mechanocytes without immunohistochemical signs of proliferation, and small areas of fibrosis without remnants of the implanted material.